Ternary chalcopyrite semiconductors : growth, electronic properties, and applications - Shay, J. L. (Joseph Leo), 1942-; Wernick, J. H. (Jack Harry), 1923- (International series of monographs in the science of the solid state, 1975)
Ternary Chalcopyrite Semiconductors: Growth, Electronic Properties, and Applications covers the developments of work in the I-III-VI2 and II-IV-V2 ternary chalcopyrite compounds. This book is composed of eight chapters that focus on the crystal growth, characterization, and applications of these compounds to optical communications systems. After briefly dealing with the status of ternary chalcopyrite compounds, this book goes on describing the crystal growth of II-IV-V2 and I-III-VI2 single crystals. Chapters 3 and 4 examine the energy band structure of these semiconductor compounds, illustrat.